2014
DOI: 10.1177/0265532214562098
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Slovenian national alignment to CEFR: The case of the B2 reading comprehension examination in English

Abstract: The paper examines the results of the CEFR alignment project for the Slovenian national examinations in English. The authors aim to validate externally the standard-setting procedures by adopting a socio-cognitive model of validation (Khalifa & Weir, 2009; Weir, 2005) to analyse the scoring, context and cognitive validity of three reading subtests: the Slovenian B2 national examination and the international examinations FCE and CAE, aligned with B2 and C1 respectively. The relative comparability between the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There have also been studies which have addressed specifically alignment processes of the CEFR into national language education contexts. Ilc and Stopar (2015), for example, addressed the alignment process of national examinations conducted in English to the CEFR proficiency descriptors in Slovenian context. The study reported significance of this kind of processes since understanding descriptors in international benchmarks such as the CEFR may contribute substantially to language teaching policies followed by countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have also been studies which have addressed specifically alignment processes of the CEFR into national language education contexts. Ilc and Stopar (2015), for example, addressed the alignment process of national examinations conducted in English to the CEFR proficiency descriptors in Slovenian context. The study reported significance of this kind of processes since understanding descriptors in international benchmarks such as the CEFR may contribute substantially to language teaching policies followed by countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pižorn (2009) also reports on the initial problems the panellists faced at the early stages of the alignment process. However, as partial external evaluations of the alignment project (Ilc and Stopar 2014) suggest, these factors had an insignificant effect on their judgements.…”
Section: Implications and Recommendationsmentioning
confidence: 96%
“…Additionally, the same tasks have been aligned with the CEFR level B2, with the cut score of 75 percent. The alignment has also been externally validated (Ilc and Stopar, 2015), and the test has also been studied with regard to item and task difficulty (Stopar and Ilc, 2016). The cut score for B1 was not set during the alignment project; therefore, we label the participants below the B2 cut score as 'sub-B2' readers.…”
Section: Instruments and Proceduresmentioning
confidence: 99%